CHINESE ESPIONAGE ACTIVITIES AGAINST THE UNITED STATES MILITARY INDUSTRY - Arindiya, Ghina; Triwahyuni, Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to analyze China’s espionage activities against the United States, especially in the military industry. In analyzing the case the author uses the concepts of the Action-Reaction Model and Information War. The espionage conflict between the US and China is influenced by the proximity and complexity of political, technological and strategic factors. The collection technique was carried out through literature study and then analyzed using qualitative methods. The results of this research show that espionage has a major influence on the complexity of cyber security. Final conclusions about Chinese espionage against America will depend largely on the actual evidence available, and these assessments are often carried out in great secrecy. However, espionage conflict is a serious problem that requires a coordinated and strategic response from the government and related institutions